Enhanced piezoelectric operation of NiO/GaN heterojunction generator by suppressed internal carrier screening. (22nd September 2017) - Jeong, Dae Kyung; Kang, Jin-Ho; Ha, Jun-Seok; Ryu, Sang-Wan
Abstract: A NiO/GaN heterojunction piezoelectric generator was fabricated, and the improvement in device performance was analyzed. The electrical properties of NiO were varied by regulating the gas environment during sputtering. An optimized NiO layer was adopted for high piezoelectric voltage generation. Internal carrier screening was revealed to be the dominant mechanism degrading the piezoelectric performance, necessitating the suppression of carrier screening. The highly resistive NiO layer was advantageous in the suppression of carrier transport across the junction that screened the piezoelectric field. The maximum piezoelectric voltage and current density values obtained were 7.55 V and 1.14 µ A cm −2, respectively. The power obtained was sufficient to operate a light-emitting diode combined with a charging circuit.